2018
DOI: 10.1037/men0000134
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of research on masculinity ideologies using all forms of the Male Role Norms Inventory (MRNI).

Abstract: Since its development in the late 1980s, the Male Role Norms Inventory (MRNI) and related forms have been used in 91 studies to examine masculinity ideologies through male role norms in the United States and other countries with over 30,000 participants. The study of male role norms and masculinity ideologies has remained a prominent area of study in the psychology of men and masculinities since at least 1995. Since the last formal review of the MRNI in 2007, 2 new forms of the MRNI have been developed, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 105 publications
4
84
1
Order By: Relevance
“…Although the CMNI is a multidimensional measure of 11 specific masculine norms, in the only meta-analysis of the CMNI in relationship to men’s health conducted to date, less than half of the included studies reported subscale results ( Wong et al, 2016 ). Studies of other masculinity constructs have reported similar results (e.g., Gerdes et al, 2017 ). This is notable considering that although the dimensionality of the CMNI has been established using confirmatory factor analysis (CFA), it has not yet been assessed whether a more general construct corresponding to the total scale score also could be represented in the CFA model of the CMNI using either a bifactor or a hierarchical model ( Kline, 2016 ).…”
Section: The Conformity To Masculine Norms Inventorysupporting
confidence: 60%
See 3 more Smart Citations
“…Although the CMNI is a multidimensional measure of 11 specific masculine norms, in the only meta-analysis of the CMNI in relationship to men’s health conducted to date, less than half of the included studies reported subscale results ( Wong et al, 2016 ). Studies of other masculinity constructs have reported similar results (e.g., Gerdes et al, 2017 ). This is notable considering that although the dimensionality of the CMNI has been established using confirmatory factor analysis (CFA), it has not yet been assessed whether a more general construct corresponding to the total scale score also could be represented in the CFA model of the CMNI using either a bifactor or a hierarchical model ( Kline, 2016 ).…”
Section: The Conformity To Masculine Norms Inventorysupporting
confidence: 60%
“…Over 500 studies conducted over at least three decades have examined outcomes related to conformity to and belief in specific identified masculine norms and related constructs in men ( Wong & Wester, 2016 ). Hundreds of findings have evidenced harmful health outcomes associated with masculine norms ( Gerdes et al, 2017 ; Wong et al, 2016 ). However, knowing how and in what ways these relationships serve to promote or risk health will depend on future research that compares total scores to subscale scores of measures of masculine norms while diversifying research methods and statistical analyses (Wong & Horn, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 1980s on, theoretical perspectives have been shifting toward the study of masculine social norms and the social construction of masculinity; in the United States, gender role conflict, gender role strain, and masculinity ideologies have stood prominently in the major theory positions and associated research (Levant & Wong, 2017). Research reviews published in the last decade generally conclude that conformity to masculine norms and gender role conflict are related to men’s psychological and interpersonal problems, which are negatively associated with men’s health and well-being (e.g., Gerdes, Alto, Jadaszewski, D’Auria, & Levant, 2018; Griffith, Gunter, & Watkins, 2012; O’Neil, 2008; Wong, Ho, Wang, & Miller, 2017), although results differed depending on the specific dimension analyzed (Gerdes & Levant, 2018; Griffith et al, 2012; Kaya, Iwamoto, Brady, Clinton, & Grivel, 2019; Wong et al, 2017).…”
mentioning
confidence: 99%